Description Of Students’ Critical Thinking Skills Throught The Use Of Ethnoscience -Based Discovery Learning Models - Lia Fadhilah; Skunda Diliarosta (Department of Science Education, 2021)
The purpose of this study is to get an overview of the students' critical thinking skills in learning using the ethnoscience-based Discovery Learning model. The type of research used is library research with analysis uses descriptive analysis. The data used in the study are secondary data in the form of scientific journals such as articles. Data collection method used in this study is the documentation method with data analysis techniques in the form of content analysis. Based on the results of a journal review that has been done, it is obtained that the use of the ethnoscience-based Discovery Learning model in learning can beraises students 'critical thinking skills by showing that students' critical thinking skills on each indicator have increased.